VALIDATION OF A SURVIVABLE PUBLISH-SUBSCRIBE SYSTEM - Singh, Sankalp; Agbaria, Adnan; Stevens, Fabrice; Courtney, Tod; Meyer, John F.; Sanders, William H.; Pal, Partha (International Journal of Computing, 2014)
We describe, with respect to high-level survivability requirements, the validation of a survivable publish subscribe system that is under development. We use a top-down approach that methodically breaks the task of validation into manageable tasks, and for each task, applies techniques best suited to its accomplishment. These efforts can be largely independent and use a variety of validation techniques, and the results, which complement and supplement each other, are seamlessly integrated to provide a convincing assurance argument. We also demonstrate the use of model-based validation techniques, as a part of the overall validation procedure, to guide the system’s design by exploring different configurations and evaluating trade-offs.